Transforming Literacy: The Impact of Chromebook and Let's Read on Elementary Students' Reading Engagement - Jeni Bastian Kamba; Muh Dliyaul Haq; Maria Dominika Niron (Universitas Pendidikan Ganesha, 2024)
Students' literacy skills in Indonesia remain a critical concern in education. The lack of reading interest, particularly among elementary school students, necessitates the integration of technology as an innovative solution in learning. This study aims to explore the impact of Chromebook and Let's Read application on students' reading interest through picture stories. A qualitative approach using a case study method was employed, involving 30 students from two elementary schools as research subjects. The results indicated a positive trend in students' engagement and enthusiasm, along with significant improvements in concentration and focus during learning activities. Teacher reports confirmed that the use of Chromebook and Let's Read significantly enhanced students' motivation to read and explore picture stories. However, the study also identified challenges such as technical issues and curriculum adjustments. Despite these obstacles, the integration of technology in education demonstrated promising outcomes in increasing students' reading interest and literacy skills. This research concludes that the use of Chromebook and Let's Read application can create a more engaging and effective learning environment, fostering active student participation in reading activities. The findings emphasize the importance of leveraging technology in elementary education to cultivate sustainable reading habits and improve literacy outcomes.